A review on the Malaysian and Indonesian batik production, challenges, and innovations in the 21st century - Syed Shaharuddin, Sharifah Imihezri; Shamsuddin, Maryam Samirah; Drahman, Mohd Hafiz; Hasan, Zaimah; Mohd Asri, Nurul Anissa; Nordin, Ahmad Amri; Mohd Shaffiar, Norhashimah (SAGE Publication, 2021)
Malaysia and Indonesia are well known as prolific producers of batik in Southeast Asia. The history of batik in both countries is deeply intertwined for more than a century. Most available published works related to batik production, challenges, and innovations were discussed within the local batik context of each country. This study aims to identify collectively how far batik, as a creative industry in these countries has progressed since its establishment until the present 21st century. It was notable that batik craftsmanships have been mostly maintained as similar tools and techniques are persistently being used until today in both countries. Significant progress was observed in the design and stylization of the batik design with the use of digital approaches such as fractal geometry. Similar challenging problems faced by both nations were highlighted and clustered into internal and external issues. It was concluded that assimilations of Third Industrial Revolution technology (IR3.0) primarily centered on the use of computer-aided design and computer-aided manufacturing to improve existing batik production. Emerging studies have shown the positive impact of integrating Fourth Industrial Revolution (IR4.0) technology such as augmented reality (AR) in promoting batik knowledge and transmitting batik as an intangible cultural heritage. The transmission of batik skills to the young generation has been a persistent problem. Thus, a brief framework was proposed to exemplify how IR4.0 technology can innovatively be used to transmit the batik skills via education platform.